Does it pay to be responsible? Evidence on corporate social responsibility and the investment performance of Australian REITs. Issue 4 (4th July 2022) - Westermann, Steffen; Niblock, Scott J.; Kortt, Michael A.
ABSTRACT: This paper creates portfolios to better understand the influence of corporate social responsibility (CSR) practices on the risk-adjusted returns of Australian Real Estate Investment Trusts (A-REITs) from 2007 to 2016. We find that A-REIT portfolios (except for the high CSR-rated portfolio) outperform the broader Asia-Pacific market. We also show that the low CSR-rated A-REIT portfolio delivers the best risk-adjusted return performance. Our findings indicate that while CSR practices might mitigate risk in A-REITs, they do not appear to improve risk-adjusted return performance. However, CSR practices may be effective in producing greater risk-adjusted returns for A-REITs during market downturns or economic crises.